A curriculum for ethnic diversity: documenting the process of change in a secondary school - Edwards, John V. (1997)
This is a case study of a project in curriculum development which was undertaken in a Berkshire secondary school between 1986 and 1990. The aim of the study is to describe, analyse, and interpret the processes which were involved in the project: the reasons why it was undertaken, the strategies which it employed, and its impact upon the institution.